MAGNETIC BEHAVIOR OF LAMELLAR MnPS3 AND CdPS3 COMPOSITES WITH A PARAMAGNETIC MANGANESE(III) MACROCYCLIC GUEST - VALENCIA,P (Sociedad Chilena de Química, 2013)
Six new composites derived from the intercalation of the MPS3 phases (M = MnII, CdIII) with the macrocyclic manganese(III) complex [MnL(H2O)2].NO3(H2O) (LH2 = Schiff base macrocyclic ligand derived from the condensation of 2-hydroxy-5-methy1-1,3-benzene-dicarbaldehyde and 1,2-diamine-benzene) were obtained by two different synthetic procedures: a conventional and a microwave assisted method. The composites [MnL]0.25K0.15Mn0.80 PS3(H2O)~1.0 (1), and [MnL]0.25K0.15Cd 0. 80PS3(H2O)~0.5 (2) were obtained by the conventional method, after stirring a suspension of the corresponding potassium precursor and the macrocyclic complex for two weeks, while [MnL]0.35K0.15Mn0.80 PS3(H2O)~1.0 (3) and [MnL]0.25K0.15Cd 0. 80PS3(H2O)~0.5 (4) after stirring for four weeks at room temperature. Using a microwave assisted reaction permitted to obtain in a shorter period of time as compared with the conventional method, composites [MnL]0.20K0.15Mn0.80 PS3(H2O)~1.0 (5) and [MnL]0.15K0.15Cd 0. 80PS3(H2O)~0.5 (6). All the M = MnII, MnIII composites show a bulk antiferromagnetic behavior. However, the spontaneous magnetization present at low temperature in the potassium precursor K0.40Mn0.80 PS3(H2O)~1.0 is observable in composite [MnL]0.20K0.15Mn0.80 PS3(H2O)~1.0 (5), while it is completely absent in composites [MnL]0.25K0.15Mn0.80 PS3(H2O)~1.0 (1) and [MnL]0.35K0.15Mn0.80 PS3(H2O)~1.0 (3).